A Study of the Effective Factors on the Women's Social Health: A Review Study in Persian Scientifi Journals - Mojhgan Firouzbakht; Mohammad-Esmaeil Riahi; Aram Tirgar (Shahid Beheshti University of Medical Sciences, 2018)
Background and objectives: Although Women's health in the physical, mental and social aspects are the most important foundation of community health, but there is a little attention to women›s social health in comparison with the other aspects. The aim of this study is investigation some of effective factors on women's social health. Material and Methods: This is a review study. The articles in Persian scientifi research journals indexed databases including SID, Magrian, Iran medex, google scholar ,Noormags and Elmnet without time limitation and with the overall keyword «social health», and more detailed keywords such as «social participation, social adaptation, social acceptance, social solidarity, social prosperity» as social health aspects, and «women» has been searched. Totally, 134 articles has been chosen and fially 20 articles approved in accordance with the objectives of the study. Results: The results showed that there was a signifiant relationship between social health and socio-economic class, education, income, social support, social capital. Conclusion: Social health especially in women, has been less considered in comparison with other aspect of health in Persian health studies. In order to obtain the highest level of health, it seems necessary to pay attention to social determinant of health along with other domain of health.